LEARNING STYLES AND LEARNING STRATEGIES IN LEARNING ENGLISH USED BY NON-ENGLISH STUDENTS - Hamliyah, Hamliyah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Non-English students of Nursing and Economics need to learn English effectively by using appropriate learning strategies that reflect their learning styles in which to achieve their learning goals. This study investigated learning styles and learning strategies in learning used by non-English students. An explanatory mixed-methods design was used involving both quantitative and qualitative data. The findings revealed that out of listening, speaking, and writing strategies, there was a statistical difference (p> 0.05) in the language learning strategies used in reading by different sensory learning styles (visual, auditory, and tactile). For personal learning styles, the use of strategies in speaking and reading employed by Extroverted-Random-Open and Introverted-Concrete-Closure of Nursing and Economics students also had statistical differences (p< 0.05). On the contrary, strategies in listening and writing used by both groups of Extroverted-Random-Open and Introverted-Concrete-Closure were no statistical differences. Meanwhile, in cognitive learning styles, there was a statistical difference (p> 0.05) in the use of strategies in speaking and reading between synoptic and etanic Science and Social Science students. These findings showed that both Nursing and Economics students used the strategies for receptive skills (listening and reading) and productive skills (speaking) in high-frequency usage except for writing strategies in the moderate range. It means that they can be categorized as language learners and users